Respuesta :
Answer:
[tex]\huge\boxed{\bf\:2 (-a - 6)}[/tex]
Step-by-step explanation:
[tex]6a - 4(2a + 3)\\6a - (4*2a + 4*3)\\6a - (8a + 12)\\6a - 8a - 12\\- 2a - 12\\\boxed{\bf\:2 (-a - 6)}[/tex]
Steps:
- Factorise the second term as the first is already in its simplified form.
- Solve the first term and the second term by doing the required arithmetic operations.
- Take the common factor out.
- The result will be : 2 (- a - 6).
[tex]\rule{150pt}{2pt}[/tex]
Answer:
[tex]\Longrightarrow: \boxed{\sf{-2a-12}}[/tex]
Step-by-step explanation:
Use the distributive property.
[tex]\underline{\text{DISTRIBUTIVE PROPERTY:}}\\\\\Longrightarrow: \sf{A(B+C)=AB+AC}[/tex]
6a-4(2a+3)
First, multiply by expand.
⇒ -4(2a+3)
⇒ -4*2a=-8a
⇒ -4*3=-12
⇒ -8a-12
→ 6a-8a-12
Solve.
Add or subtract the numbers from left to right.
⇒ 6a-8a=-2a
= -2a-12
[tex]\Longrightarrow: \boxed{\sf{-2a-12}}[/tex]
- Therefore, the correct answer is -2a-12.
I hope this helps! Let me know if you have any questions.